Phytosterols and Omega 3 Supplementation Exert Novel Regulatory Effects on Metabolic and Inflammatory Pathways: A Proteomic Study - Lambert, Carmen (Nutrients, 2017)
Cardiovascular disease (CVD) remains one of the major causes of death and disability worldwide. In addition to drug treatment, nutritional interventions or supplementations are becoming a health strategy for CVD prevention. Phytosterols (PhyS) are natural components that have been shown to reduce cholesterol levels; while poly-unsaturated fatty acids (PUFA), mainly omega-3 (ω3) fatty acids, have shown to reduce triglyceride levels. Here we aimed to investigate whether the proteins in the main lipoproteins (low density lipoproteins (LDL) and high density lipoproteins (HDL)) as well as proteins in the lipid free plasma fraction (LPDP) were regulated by the intake of PhyS-milk or ω3-milk, in overweight healthy volunteers by a proteomic based systems biology approach. The study was a longitudinal crossover trial, including thirty-two healthy volunteers with body mass index (BMI) 25–35 kg/m(2) (Clinical Trial: ISRCTN78753338). Basal samples before any intervention and after 4 weeks of intake of PhyS or ω3-milk were analyzed. Proteomic profiling by two dimensional electrophoresis (2-DE) followed by mass spectrometry-(MALDI/TOF), ELISA, Western blot, conventional biochemical analysis, and in-silico bioinformatics were performed. The intake of PhyS-milk did not induce changes in the lipid associated plasma protein fraction, whereas ω3-milk significantly increased apolipoprotein (Apo)- E LDL content (p = 0.043) and induced a coordinated increase in several HDL-associated proteins, Apo A–I, lecitin cholesterol acyltransferase (LCAT), paraoxonase-1 (PON-1), Apo D, and Apo L1 (p < 0.05 for all). Interestingly, PhyS-milk intake induced a reduction in inflammatory molecules not seen after ω3-milk intake. Serum amyloid P component (SAP) was reduced in the LPDP protein fraction (p = 0.001) of subjects taking PhyS-milk and C-C motif chemokine 2 (CCL2)expression detected by reverse transcription polymerase chain reaction (RT-PCR) analysis in white blood cells was significantly reduced (p = 0.013). No changes were observed in the lipid-free plasma proteome with ω3-milk. Our study provides novel results and highlights that the PhyS-milk induces attenuation of the pro-inflammatory pathways, whereas ω3-milk induces improvement in lipid metabolic pathways.